Externality of Retailing and Regional Contribution - Takemasa Ishihara (Maketingu Janaru, 2019)
The regional contributions of retailers are gaining a lot of attention, and this is by no means an “unnecessary task unrelated to the original work” of the retailer. Rather, it is a legitimate assessment of externality that the store-type retailer originally had. Consideration of externalities and the main retail business, which has been both sides of the same coin, have been separated with development of chain store operations. External regulation, including that by the local government, was a step toward a new norm for retailers. Chain-type retailers are also working on a number of community contribution activities, but it is important to tackle “town development” together with local retailers, and not with companies alone.